High-Speed Free-Space Optical Continuous Variable-Quantum Key Distribution Based on Kramers–Kronig Scheme - Zhen Qu; Ivan B. Djordjevic (IEEE Photonics Journal, 2018)
We propose and experimentally investigate a high-speed Kramers–Kronig (KK) scheme based continuous-variable quantum key distribution (CV-QKD) system over a free-space optical (FSO) channel. The atmospheric turbulence channel is emulated by three spatial light modulators on which three randomly generated azimuthal phase patterns yielding Andrews’ spectrum are recorded. The proposed KK scheme enables a low-complexity implementation, insensitivity to laser phase noise, low detection noise, and accurate channel transmittance monitoring. In addition, eight state CV-QKD protocols and 10-channels wavelength-division multiplexing (WDM) scheme are experimentally verified to obtain a high secure key rate. In our experiment, the minimum transmittance of 0.6 is required to guarantee the secure transmission, and a total SKR of 2.1 Gb/s can be obtained at the mean transmittance in weak turbulence regime.